2022
DOI: 10.1021/acs.inorgchem.2c02807
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Tuning, Pressure, and Temperature Behavior of Mn4+ Photoluminescence in Ga2O3–Al2O3 Alloys

Abstract: In this study, we carried out a detailed investigation of the photoluminescence of Mn4+ in Ga2O3–Al2O3 solid solutions as a function of the chemical composition, temperature, and hydrostatic pressure. For this purpose, a series of (Al1–x Ga x )2O3:Mn4+,Mg phosphors (x = 0, ..., 0.1.0) were synthesized and characterized for the first time. A detailed crystal structure analysis of the obtained materials was done by the powder X-ray diffraction technique. The results of the crystal structure and luminescence stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
2
6
0
Order By: Relevance
“…In addition, the position of the PL peaks slightly blue-shifts (for example, the ZPL shifts from 623.1 nm for the x = 0.97 sample to 621.7 nm for the x = 0.50 sample) with the decreasing Si 4+ concentration, which could be due to the enhancement of the crystal field around the Mn 4+ ion. 18 Similar to h-K 2 MnF 6 reported by Adachi, 19 the K 2 MnF 6 :Si 4+ , NH 4…”
Section: Methodssupporting
confidence: 68%
“…In addition, the position of the PL peaks slightly blue-shifts (for example, the ZPL shifts from 623.1 nm for the x = 0.97 sample to 621.7 nm for the x = 0.50 sample) with the decreasing Si 4+ concentration, which could be due to the enhancement of the crystal field around the Mn 4+ ion. 18 Similar to h-K 2 MnF 6 reported by Adachi, 19 the K 2 MnF 6 :Si 4+ , NH 4…”
Section: Methodssupporting
confidence: 68%
“…Unlike Cr 3+ , Mn 4+ in inorganic hosts was observed only under high crystal field conditions, thus always exhibiting the 2 E -4 A 2 emission. The pressure shift of the 2 E emission of Mn 4+ was observed for Al 2 O 3 , 35 39 and a collection of tungstate 40 and fluoride hosts. 22,23,[41][42][43] Most of these reports, however, lack a detailed discussion of pressure influence on parameters (Dq, B, and C) determining the energy structure of Mn 4+ , except for ref.…”
Section: Introductionmentioning
confidence: 92%
“…Adachi 44 performed an analysis of Racah parameters of Mn 4+ in KNaSiF 6 :Mn 4+ according to his modified approach, based on the energies of 2 E and 4 T 2 subterms. Zhydachevskyy et al 39 showed an appealing similarity between the effects of the mechanical pressure of Ga 2 O 3 :Mn 4+ and the chemical pressure obtained by creating (Al,Ga) 2 O 3 :Mn 4+ solid solutions. Zheng et al 45 reported Mn 4+ in Gd 2 ZnTiO 6 double perovskite as a bifunctional luminescent pressure and temperature sensor.…”
Section: Introductionmentioning
confidence: 95%
“…Mn 3+ typically does not luminesce, as heavily Jahn-Teller distorted species tend to have sufficient non-radiative pathways for relaxation [12]. Mn 4+ is also unlikely to be responsible, since Zhydachevskyy et al demonstrated an emission around 710 nm for Mn 4+ doped β-Ga2O3 [18]. This assignment is supported by changes in the intensity of the luminescence following an anneal at 1000 ⁰C for 15 hours in flowing O2.…”
Section: Pleochroism In Doped β-Ga2o3mentioning
confidence: 99%
“…It has been thoroughly shown that Cr 3+ in β-Ga2O3 occupies the octahedral site and displays a similar absorption spectrum to ruby, albeit shifted in energy so that a deep green coloration is exhibited [13]. This is due to the weaker crystal field compared to ruby, as is the case with Cr 3+ in emerald [1,18]. While ruby is uniaxial, thus showing two distinct colors in polarized light, β-Ga2O3 is biaxial, displaying three distinct absorptions as shown in Figure 3.…”
Section: Pleochroism In Doped β-Ga2o3mentioning
confidence: 99%